Sex disparities in salivary malignancies: Does female sex impact oncological outcome?. (July 2019) - Mimica, Ximena; McGill, Marlena; Hay, Ashley; Zanoni, Daniella Karassawa; Shah, Jatin P.; Wong, Richard J.; Ho, Alan L.; Cohen, Marc A.; Patel, Snehal G.; Ganly, Ian
Highlights: Female patients presented with early stage disease and low risk histologies. Sex, CCI, histological risk group and AJCC stage were independent predictors of DSS. Sex differences in survival were observed in the high histological risk group. Abstract: Objective: Previous population-based studies in salivary gland carcinomas have described a relationship between female sex and superior oncological outcome. Patients and methods: Our institutional database of 884 surgically treated patients with salivary gland malignancies from 1985 to 2015 was analyzed for the impact of sex on oncological outcomes. Histologies were classified in three risk groups, low, intermediate and high. Survival outcomes were determined using the Kaplan-Meier method. Hazard ratios for male sex were determined using the Cox proportional hazards model. Results: Eight hundred sixty-seven patients were identified; median age was 59 years, and 51% had a minor salivary gland malignancy. Female patients were younger (58 versus 60 years; p = 0.040) and had a lower incidence of high-risk histologies (25% versus 40%, p < 0.001) and T3-T4 tumors compared to men (23% versus 31%, p < 0.001). With a median follow-up of 57 months, female patients had a superior 5-year disease-specific survival (DSS) (90% versus 79%; p < 0.001). The unadjusted hazard ratio showed male patients had a 2.15-fold increased risk of death (HR 2.15; 95% CI, 1.50–3.06, p < 0.001). After adjusting for Charlson comorbidity index, tobacco use, histological risk group, and overall pathological stage, males still had a statistically significant increased risk of death (HR 1.48; 95% CI 1.05–2.17; p = 0.047). Subgroup analysis showed DSS for females was significantly better in the high-risk histological group (5-year 68% versus 49%, p = 0.007). Conclusion: Our study shows that sex has an impact on cancer-specific survival and that female sex favors improved survival.